Os encontros de psicólogos da área de educação (1980-1982): um projeto de psicologia escolar e educacional em São Paulo - Prates, Eduardo Freitas (2015)
The purpose of this research is to investigate The Psychologists Meetings in the Area of Education, a combination of three events held in the early 1980 s at Instituto Sedes Sapientiae in São Paulo with the organization of Sindicato dos Psicólogos do Estado de São Paulo (SPESP) and Conselho Regional de Psicologia da 6ª Região (CRP-06). The investigation had, as its historical-philosophical base, the historical and dialectical materialism, utilized to biographical and, principally, documentary researches, which procedures were conducted by methodological principles of Italian micro-history. These occasions are an expression of the political organization of psychologists in the late 1970 s that appropriated the entities of the category in the early 1980 s and proposed an ethical-political psychology project based on a critical reading of the profession, comprehended as socially committed with the low income classes. It is from this movement that an Education Committee arises, responsible for the discussion of psychology in education, which has as initiative to arrange the psychologists, through meetings which, in turn, enabled a school and educational psychology project. These events represent a remarkable moment of political organization and critical discussions, as well as a historical synthesis of experiments in educational psychology, whereupon Sérgio Antonio da Silva Leite and Yvonne Alvarenga Gonçalves Khouri stand out for their importance. We conclude that the meetings are products of the ethical-political psychology project, as are producers of a school and educational psychology project, becoming a significant historical fact of the psychology historiography in São Paulo